2011
DOI: 10.1111/j.1478-3231.2011.02554.x
|View full text |Cite
|
Sign up to set email alerts
|

A Src family kinase inhibitor improves survival in experimental acute liver failure associated with elevated cerebral and circulating vascular endothelial growth factor levels

Abstract: Background and aims Acute liver failure (ALF) is frequently complicated by cerebral edema, systemic inflammation and multi-organ dysfunction. Vascular endothelial growth factor (VEGF) may stimulate liver regeneration but can also be pro-inflammatory, activating endothelial cells and increasing permeability, actions mediated through Src kinase signalling. We therefore examined whether a Src inhibitor could have therapeutic potential in ALF. Methods Murine ALF was induced with azoxymethane. Liver pathology was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…Nevertheless, we cannot exclude the possibility that Src kinase also causes renal injury through its effects on renal microvascular permeability. In this context, it has been demonstrated that Src mediates vascular endothelial permeability responses to TNF, reactive oxygen species, angiogenesis and vascular leakage [ 25 27 ]. Disruption of endothelial cell-cell contact [ 42 ] and alteration of cell-cell adhesion complexes [ 43 ] has also been observed in a model of ischemic AKI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, we cannot exclude the possibility that Src kinase also causes renal injury through its effects on renal microvascular permeability. In this context, it has been demonstrated that Src mediates vascular endothelial permeability responses to TNF, reactive oxygen species, angiogenesis and vascular leakage [ 25 27 ]. Disruption of endothelial cell-cell contact [ 42 ] and alteration of cell-cell adhesion complexes [ 43 ] has also been observed in a model of ischemic AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Paul et al first demonstrated that mice deficient in Src were resistant to ischemic injury, and administration of Src inhibitors PP1 or PP2 to wild-type animals reduced ischemic injury in the brain [ 22 24 ]; Weis et al showed that the genetic or pharmacological blockade of Src reduced edema and tissue injury following myocardial infarction [ 24 ]. Moreover, early use of a Src inhibitor reduced hepatocellular injury and enabled survival in a murine model of acute liver failure induced by azoxymethane [ 25 ]. Finally, Src tyrosine kinase inhibition prevents I/R-induced acute lung injury [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hyperammonemia is also frequently complicated by systemic inflammation including increasing systemic and cerebral levels of vascular endothelial growth factor (VEGF), Tumor Necrosis Factor (TNF)-alpha and the interleukins (IL)-1beta and IL-6 [ 46 ]. The VEGF may stimulate liver regeneration but it can also be pro-inflammatory, activating endothelial cells and increasing permeability, actions mediated through Src kinase signaling [ 47 ]. These proinflammatory cytokines progress in parallel with the severity of astrocyte swelling [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Additionally, activation of intracellular signaling systems, including c-fos, 26 mitogen-activated protein kinases, 26 protein kinase G, 27 Src kinase family, 28 ciliary neurotrophic factor, 26 and the transcription factors p53, 29 SP-1 26 and nuclear factor-kappaB (NF-kB) [30][31][32] have all been shown to be involved in the mechanism of ammonia neurotoxicity, particularly in neuroinflammation.…”
Section: Mechanisms Of Ammonia Neurotoxicitymentioning
confidence: 99%